Torymus sinensis: a viable management option for the biological control of Dryocosmus kuriphilus in Europe? - Gibbs, Melanie; Schoenrogge, Karsten; Alma, Alberto; Melika, George; Quacchia, Ambra; Stone, Graham N; Aebi, Alexandre (My University, 2011)
The chestnut gall wasp Dryocosmus kuriphilus is a global pest of chestnut (Castanea spp). Established as a pest in the mid-twentieth century in Japan, Korea and North America, this species was first reported in Europe in 2002. Following the successful release of a biological control agent Torymus sinensis in Japan, this parasitoid species has been released in Italy since 2005. Here we discuss the potential of T. sinensis as a viable management option for the biological control of D. kuriphilus in central Europe. We suggest that more consideration should be given to determining, (i) the conditions under which T. sinensis may attack alternative native gall wasp hosts and (ii) the likelihood of hybridization of this species with native Torymus. Both issues are central to predicting unassisted range expansion by released T. sinensis, and to assess the environmental risks associated with a more widespread release of this species in Europe.
Keywords: Alien species; Biological control agent; Environmental risk assessment; Exotic species; Invasive species; Non-target effects